Environmental lead exposure: a public health problem of global dimensions - Shilu Tong; Yasmin E. von Schirnding; Tippawan Prapamontol (The World Health Organization, 2000)
Lead is the most abundant of the heavy metals in the Earth's crust. It has been used since prehistoric times, and has become widely distributed and mobilized in the environment. Exposure to and uptake of this non-essential element have consequently increased. Both occupational and environmental exposures to lead remain a serious problem in many developing and industrializing countries, as well as in some developed countries. In most developed countries, however, introduction of lead into the human environment has decreased in recent years, largely due to public health campaigns and a decline in its commercial usage, particularly in petrol. Acute lead poisoning has become rare in such countries, but chronic exposure to low levels of the metal is still a public health issue, especially among some minorities and socioeconomically disadvantaged groups. In developing countries, awareness of the public health impact of exposure to lead is growing but relatively few of these countries have introduced policies and regulations for significantly combating the problem. This article reviews the nature and importance of environmental exposure to lead in developing and developed countries, outlining past actions, and indicating requirements for future policy responses and interventions.